2017
DOI: 10.1186/s13104-017-2452-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with female anal sex in the context of HIV/AIDS in the selected districts of Tanzania

Abstract: BackgroundFemale anal sex is a receptive type of sexual practice among heterosexual couples where the penis is inserted into the anus of a female partner. In the Western world, a number of studies and interventions have been carried out on anal sex among men due to its potential risks to HIV transmission. In African countries, including Tanzania, there is dearth of information on the risks inherent in practices associated with female anal sex in the general population. The objective of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…Studies have shown that anal intercourse carries one of the highest-risk of sexual activity for getting HIV. Our results suggest that anal intercourse not only increases the risk of HIV acquisition but also from T. pallidum, and the same infection mechanism can be applied to men who have sex with men and heterosexuals [14,23,24].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Studies have shown that anal intercourse carries one of the highest-risk of sexual activity for getting HIV. Our results suggest that anal intercourse not only increases the risk of HIV acquisition but also from T. pallidum, and the same infection mechanism can be applied to men who have sex with men and heterosexuals [14,23,24].…”
Section: Discussionmentioning
confidence: 73%
“…Having anal sex with high frequency (> 50% of sexual encounters) during the last year was another factor that increased the prevalence of syphilis infection. Anal intercourse increases the risk of STIs because of the characteristic of the rectum, which shows a delicate tissue that can be easily damaged, which is aggravated by the limited lubrification, giving access to bacteria and virus to the bloodstream [22][23][24]. Studies have shown that anal intercourse carries one of the highest-risk of sexual activity for getting HIV.…”
Section: Discussionmentioning
confidence: 99%
“…One Nigerian publication out of the 38 articles reported the prevalence of oral and anal sex as a combined outcome [43]. Six articles were mixed method studies (a study each from Ethiopia, Kenya, Nigeria, Tanzania, Zambia and another was conducted in Kenya and Rwanda) [39, 66, 70, 90, 120, 133]. Fifty-nine studies were from Southern Africa, 38 were from East Africa, 20 were from West Africa and four were from Central Africa (Additional file 2: Table S1).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…With regards to anal sex, the highest prevalence in SSA among people not coming from high-risk groups was found in high-school students in Ethiopia among whom 57% reported anal practices [44], but other studies have found lower prevalences [8,10,16,17,43,4749]. One out of five sexually active people attending VCT in Kinshasa reported anal intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of oral sex comes mainly from young people and ranges from 8% to 52% [4345], although some particular studies have shown even higher frequencies [46]. Regarding anal sex, figures range from 4% to 57% [8,16,17,43,44,4750], with most of the information coming from South African studies.…”
Section: Introductionmentioning
confidence: 99%